Penerapan Hukum Positif Indonesia terhadap Tindak Pidana Penyanderaan Warga Negara Asing di Indonesia - Nurmagfirah M Zain; Mohamad Rusdiyanto U. Puluhulawa2; Julisa Aprilia Kaluku (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
This research aims to determine the application of Indonesian positive law to the crime of taking foreign citizens hostage in Indonesia. This research is classified as normative legal research with a statutory approach and a case approach. Legal materials are collected through literature study, then analyzed prescriptively. The research results show that the criminal act of taking foreign citizens hostage, in this case a pilot from New Zealand in Indonesia, is an unlawful act. The legal regulations that were violated by the crime of taking hostages were Article 6 of Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning the Establishment of Government Regulations in Lieu of Law Number 1 of 2002 concerning the Eradication of Criminal Acts. Terrorism Becomes Law and Article 451 of Law Number 1 of 2023 concerning the Criminal Code.